The Effect of Risk Management, Technological Innovation, and Human Resources Quality on Construction Project Performance in Jakarta Case Study on Government Infrastructure Projects - Loso Judijanto; Eko Sudarmanto; Thitus Gilaa (North Press, 2024)
This study examines the effect of risk management, technological innovation, and human resource quality on the performance of government infrastructure construction projects in Jakarta. Using a quantitative research design, data were collected from 70 key personnel involved in these projects. The data were analyzed using SPSS version 26, with multiple regression and correlation analysis employed to test the relationships between the variables. The results indicate that all three factors – risk management, technological innovation, and human resource quality – significantly and positively influence project performance. Human resource quality had the strongest effect, followed by risk management and technological innovation. These findings suggest that improving these factors can enhance the success of large-scale government infrastructure projects in Jakarta, providing valuable insights for construction managers and policymakers.